37 Decrease in mace rates associated with drug eluting stent use in patients with diabetes undergoing PCI in large diameter coronary arteries. (9th June 2011) - Dixit, A; Nair, S; Williams, P; Wiper, A; Clarke, B; Deaton, C; El-Omar, M; Fraser, D; Khattar, R; Mahadevan, V; Neyses, L; Ordoubadi, F; et al.
Abstract : Introduction: Both large multi centre trials and registry studies have demonstrated that PCI with drug eluting stents (DES) is associated with reduced MACE and restenosis rates compared to bare metal stents (BMS) in native coronary vessels, although this benefit is less evident in those patients with a larger coronary vessel diameter and MACE rates may actually paradoxically increase in this cohort as observed in the BASKET trial. In diabetic patients, a similar or even greater absolute reduction in MACE rates / restenosis risk is seen associated with DES use, although it is unclear as to whether any benefit persists in those with larger diameter native coronary vessels. Previous data derived from diabetic patients in large diameter native coronary vessels has come from registry studies in which numbers were either small (<200 patients) or were from highly selected patient sub groups excluding high-risk individuals (SCAAR registry). Methods: We therefore retrospectively studied 1165 consecutive diabetic patients with target vessel diameter ≥3 mm admitted to our centre for PCI from 2003 to 2009, the largest series of its kind to date. Primary endpoint was defined as total mortality and secondary endpoint was major adverse cardiac event (MACE) defined as composite endpoint of Death, Stroke, MI, Stent Thrombosis and Target Lesion / Vessel Re-Vascularisation. Results: Of the 1165 patients studied, 170 had BMS and 995 had DES. Mean follow-up period was 43.3±21.8 months (median 41.8 months). 73.5% were male in the BMS cohort vs 73.1% in the DES cohort (p>0.05). Mean age was 62.8±11.2 in BMS and 62.3± 10.4 years old in DES (p=0.55). Other demographic parameters were similar in both groups. There were a total of 23/170 deaths in BMS cohort (13.5%) and 91/995 in DES cohort (9.1%), (HR 1.38; 95% CI 0.83 to 2.27, p=0.21). A total of 42/170 (24.7%) and 163/995 (16.3%) MACE events were observed in the BMS and DES cohort respectively (HR 1.49; 1.02 to 2.19, p=0.04). Multivariate analysis illustrated that use of BMS was independently associated with increased risk of MACE (HR 1.54; 95% CI 1.05 to 2.25, p=0.03), driven through an increase in revascularisation. Conclusion: In conclusion, in one of the largest analyses of its kind, use of DES in patients with diabetes in a real world setting undergoing PCI in large diameter coronary vessels (≥3 mm) is safe and is independently associated with a reduction in MACE events. This is in contrast to that of non-diabetic patients where the benefits of DES in large diameter coronary vessels are less evident.